The impact of financial mechanisms on increasing the efficiency of small businesses and private entrepreneurship - E., Ernazarov N.; Ugli, Kodirov Yusufbek Suyunbek (Goodwood Publishing, 2025)
Purpose: This study investigates the impact of financial mechanisms on improving the efficiency of small businesses and private entrepreneurship, focusing on their role in economic development in Uzbekistan, particularly in the Samarkand region. Methodology: A mixed-methods approach was employed, integrating quantitative analysis of official statistics with historical-comparative and financial performance evaluations. Data were collected from national and regional reports, and descriptive statistics were used to assess trends in gross regional product contributions and business activity levels. Results: The findings demonstrate that small businesses consistently contribute more than 70% to the gross regional product and play a vital role in employment and industrial output. However, persistent challenges in financial accessibility, regulatory implementation, and innovation hinder full potential. The study recommends enhancing financial infrastructure, expanding credit options, and improving entrepreneurial education to support long-term sectoral growth.